Pediatric tuberculosis in close contacts: prospective study - Dr. Bonela Saikumar; Dr. Pikala Tarakeswara Rao (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Tuberculosis continues to be a major cause of morbidity and mortality among children in developing country like India. Early detection and treatment of infection can reduce morbidity and mortality. Screening of children in close contact with high risk groups is universally recommended but seldom practiced in resource limited settings. Aims and objectives: Primary objective to find prevalence of tubercular infection in children who are household contacts of PTB, and HIV-PTB co-infected adults. To identify subset of contacts who are at higher risk of contacting infection. Settings and Design: Prospective study conducted in tertiary care center. Children aged <10years in contact with adult PTB and PTB with HIV were enrolled and evaluated for tuberculosis infection by clinical, radiographic, and tuberculin testing. Transverse in duration of greater than 10 mm was defined as positive tuberculin test suggestive of tubercular infection. Results: About 33.6% of contacts exposed were found to be infected. Tuberculin test was found to be significantly positive in contacts exposed to PTB and HIV-PTB co-infected adults groups (p > 0.0001, with an odds ratio of 0.36 (1.10 - 1.74)), P>0.0001, 2.77 (1.33 - 5.79). Majority of children exposed to HIV negative PTB adults were infected compared to contacts exposed to HIV-PTB co-infected adults (35 vs 14) and the difference is statistically significant (p>0.001). Absence of scar is not associated with any significant risk. Conclusions: Prevalence of tuberculosis is high in contacts with high risk groups. HIV-PTB co-infected adults transmit infection less in comparison to HIV negative TB adults. Young children and those with severe malnutrition need to be targeted in contact screening.